Application of negative binomial regression in analyzing factors that influence stunting in toddlers - Tamimi, Allifiyani; Husein, Ismail (Desimal: Jurnal Matematika, 2024)
Stunting is a growth and development disorder caused by a lack of nutrition. This research aims to determine the significant factors that influence cases of stunting among toddlers in North Sumatra province in 2022. By using Negative Binomial Regression, we obtained factors that have a significant influence on the incidence of stunting among toddlers in North Sumatra province. The research results obtained show that the variables of the number of toddlers who are given exclusive breastfeeding, the number of toddlers who have inadequate access to sanitation, and the number of toddlers who receive Complete Basic Immunization will have a significant effect on stunting cases in toddlers in Sumatra Province in 2022. This can be seen from the P-values of each variable that significantly influences the incidence of stunting in toddlers: 0.0285 (x1), 0.0525 (x3), and 0.0452 (x6).